Burnout Factors in Private Health and Fitness Centers' Sector: A Case Study in Greece - Yannis Georgiou; Aggeliki Fotiou (University of Montenegro, Faculty for Sport and Physical Education, Montenegrin Sports Academy, 2019)
The aim of the research was to investigate conceiving levels of Burnout, in employees in private fi tness and health centers of the prefecture of Attica, Greece in relation with demographic factors such as gender, age, familial situation and level of education. Participants (n=185) answered in a demographic questionnaire and the MBI-GS (Maslach Burnout Inventory-General Survey) questionnaire in 16 questions, in reference to the three factors of the Burnout Syndrome, Emotional Exhaustion, Depersonalization, and Personal Accomplishments. The analysis of variation (ANOVA), did not show any signifi cant statistical differences between the independent variables and the three factors of the dependent one. However, the agreement of results of the present research, with similar research in the public sector, as well as the diff erences that are presented concerning other occupational groups, tend in the aff air of the relation of the content of work and environmental labor factors that are perhaps connected with the existence of Burnout.